2004
DOI: 10.1534/genetics.103.025379
|View full text |Cite
|
Sign up to set email alerts
|

The GanB Gα-Protein Negatively Regulates Asexual Sporulation and Plays a Positive Role in Conidial Germination in Aspergillus nidulansSequence data from this article have been deposited with the EMBL/GenBank Data Libraries under accession no. AF198116.

Abstract: We isolated the ganB gene encoding the G␣-protein homolog from Aspergillus nidulans. To investigate the cellular function of GanB, various mutant strains were isolated. Deletion of constitutively inactive ganB mutants showed conidiation and derepressed brlA expression in a submerged culture. Constitutive activation of GanB caused a reduction in hyphal growth and a severe defect in asexual sporulation. We therefore propose that GanB may negatively regulate asexual sporulation through the BrlA pathway. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
116
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 52 publications
5
116
0
2
Order By: Relevance
“…FluG activates asexual development by removing repressive effects imposed by multiple negative regulators (Seo et al 2003), resulting in activation of a key transcription factor BrlA (see Adams et al 1998). Genetic data suggest that GanB (Chang et al 2004) and SfaD (Yu et al 1996;Rosén et al 1999) function in negative regulation of conidiation under submerged culture conditions. It is further speculated that FadA and SfaDTGpgA may also function in signaling for sexual fruiting body development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FluG activates asexual development by removing repressive effects imposed by multiple negative regulators (Seo et al 2003), resulting in activation of a key transcription factor BrlA (see Adams et al 1998). Genetic data suggest that GanB (Chang et al 2004) and SfaD (Yu et al 1996;Rosén et al 1999) function in negative regulation of conidiation under submerged culture conditions. It is further speculated that FadA and SfaDTGpgA may also function in signaling for sexual fruiting body development.…”
Section: Discussionmentioning
confidence: 99%
“…(dominant negative allele), DsfaD, and the absence of GanB (another Ga) functions suggest that GanB and SfaD play a role in negative regulation of conidiation under submerged culture conditions (Rosén et al 1999;Chang et al 2004;Han et al 2004b).…”
Section: G203rmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The gasC orthologues, rasA, and cflA are also important for conidial germination in the taxonomically closest model fungus Aspergillus nidulans, in Botrytis cinerea, and in a variety of other fungal species (3,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Genomic sequencing has revealed that most filamentous ascomycetes have three Ga-subunits (Liu and Dean 1997;Chang et al 2004;Kays and Borkovich 2004). Among them, Ga-subunits of the fungal group I share specific sequence similarities with the mammalian G i subunits, while the subunits of group III have been assigned as G s subunits on the basis of their functionality in stimulating adenylyl cyclases like their mammalian counterparts.…”
mentioning
confidence: 99%